The effects of inflammation and anti-inflammatory treatment on lipid metabolism and liver morphology in a rheumatoid arthritis rat model - Denga, Tshimangadzo Moreblessings (My University, 2021)
High-grade inflammation plays a key role in the development of dyslipidaemia in rheumatoid arthritis (RA) patients. Biologic disease-modifying antirheumatic drugs (DMARDs), for example TNF-α inhibitors and IL-6 receptor blockers, are used to mitigate systemic inflammation. However, the effect of these DMARDs on lipid metabolism is inconsistent. Additionally, these drugs have been associated with liver dysfunction in RA, however, these mechanisms are unclear. This study aimed to determine the effect of inflammation and biologic DMARD treatments on lipid metabolism and liver morphology in the collagen induced arthritis (CIA) rat model. Three-month-old male (n=38) and female (n=30) Sprague-Dawley rats were randomly divided into the control (n=20), inflammation (n=18), TNF-α inhibitor (n=15) and IL-6 blocker (n=15) groups. To induce arthritis, bovine type-II collagen emulsified in incomplete Freund's adjuvant was injected at the base of the tail, in the inflammation, TNF-α inhibitor and IL-6 blocker groups. At the first signs of arthritis, rats in the TNF-α inhibitor group received 10mg/kg intraperitoneal injections of Etanercept (a TNF-α inhibitor), every third day for six weeks and rats in the IL-6 blocker group received 8mg/kg intraperitoneal injections of Tocilizumab (an IL-6 receptor blocker), once a week for six weeks. At termination, body weight, tail-cuff blood pressure, arthritis scores and paw thickness were assessed. Serum concentrations of glucose, triglycerides, high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C) were measured. The TNF-α, IL-6, C-reactive protein (CRP), and ATP-binding cassette transporter A1 (ABCA1) serum concentrations were measured using enzyme-linked immunosorbent assays (ELISA). Liver lipid content was determined using the Soxhlet technique and liver steatosis was determined by histological haematoxylin and eosin (H&E) staining. Liver fibrosis was determined by histological Masson’s trichrome and picrosirius red staining. Liver enzymes, aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase (ALP) were measured using the IDEXX colorimetric chemistry analyser. Group differences in serum lipid profile, iv liver morphology and inflammatory markers were assessed using a two-way analysis of variance (ANOVA) with a Tukey post-hoc test. Associations between inflammatory markers with markers of liver fibrosis and liver toxicity were determined by Pearson’s correlations. There were no significant differences in body weight or tail-cuff blood pressure between the groups at termination (all p>0.05). The HDL-C concentrations were lower in the inflammation (6.16 ± 0.34μM; p<0.0001) and TNF-α inhibitor groups (7.07 ± 0.37μM; p=0.0004) compared to the control group (9.17 ± 0.32μM). The HDL-C concentrations were higher in the IL-6 blocker group (8.10 ± 0.43μM; p=0.004) compared to the inflammation group (6.16 ± 0.34μM). The ABCA1 concentrations were lower in the inflammation group (1.53 ± 0.26 ng/ml; p=0.04) compared to the control group (2.44 ± 0.22ng/ml). The ABCA1 concentrations were higher in the TNF-α inhibitor (3.00 ± 0.25 ng/ml; p=0.0007) and IL-6 blocker groups (3.28 ± 0.26 ng/ml; p<0.0001) compared to the inflammation group (1.53 ± 0.26 ng/ml; p=0.04). There were no differences in serum concentrations of glucose, triglycerides, LDL-C or markers of liver steatosis between the groups (all p>0.05). Liver lipid content was significantly lower in the inflammation (6.79 ± 0.40%; p<0.0001), TNF-α inhibitor (6.90 ± 0.40%; p<0.0001) and IL-6 blocker (8.03 ± 0.35%; p=0.01) groups compared to the control group (9.68 ± 0.36%). There were no significant differences in liver fibrosis or liver toxicity enzyme markers between the control and inflammation groups (all p>0.05). Markers of liver fibrosis were significantly higher in the TNF-α inhibitor (Masson’s trichrome collagen area fraction: 2.81 ± 0.31%; <0.0001, picrosirius red collagen area fraction: 2.37 ± 0.23%; p=0.03) and IL-6 blocker (Masson’s trichrome collagen area fraction: 3.04 ± 0.25%; p<0.0001, picrosirius red collagen area fraction: 2.91 ± 0.21%; p<0.0001) groups compared to the control group (Masson’s trichrome collagen area fraction: 1.19 ± 0.12%, picrosirius red collagen area fraction: 1.51 ± 0.18%; p=0.03 and p<0.0001 respectively) and the inflammation group (Masson’s trichrome collagen area fraction: 1.82 ± 0.24%, picrosirius red collagen area fraction: 1.95 ± 0.16%, p=0.03 and p=0.004 respectively). The serum concentrations of ALP were significantly higher in the TNF-α inhibitor (116 ± 5.81μl; p=0.02) v and IL-6 blocker (141.85 ± 9.38μL; p<0.0001) groups compared to the control group (87.16 ± 4.96μl). The serum concentrations of ALP were significantly higher in the IL-6 blocker group (141.85 ± 9.38μl) compared to the inflammation group (103.16 ± 6.97μl; p=0.001). In conclusion, chronic inflammation impaired the serum concentrations of HDL-C, ABCA1 and liver lipid content in the CIA rat model. Although TNF-α inhibitor therapy improved the inflammation-induced changes in ABCA1, TNF-α inhibitors induced liver fibrosis and increased the ALP concentration. Despite improving the overall lipid profiles of rats exposed to CIA, IL-6 receptor blockers also induced liver fibrosis and liver toxicity. Although biologic anti-inflammatory drugs may ameliorate inflammation-induced alterations in lipid metabolism, the potential adverse effect on the liver highlights the need for further investigation.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, School of Physiology, University of the Witwatersrand, Johannesburg, 2021